2013
DOI: 10.1155/2013/673078
|View full text |Cite
|
Sign up to set email alerts
|

Add-On Effect of Chinese Herbal Medicine Bath to Phototherapy for Psoriasis Vulgaris: A Systematic Review

Abstract: Psoriasis vulgaris is the most common form of psoriasis. Phototherapy has been proven effective for psoriasis, but side effects have become a concern. Chinese herbal medicine (CHM) bath combined with phototherapy has been used in clinical settings, but the additional benefit requires evaluation. This review aims to evaluate the additional benefit and safety of adding CHM bath to phototherapy for psoriasis vulgaris. Cochrane library, PubMed, Embase, CNKI, and CQVIP were searched from their inceptions to 6 Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Consequently, to find more effective therapeutic methods to prevent the return of disease activity many individuals have turned their attention to treatments such as TCM. Currently, clinical experience has been accumulated for TCM treatment of psoriasis [13][14][15][16][17][18][19][50][51][52]. Most significantly, as a type of TCM, acupuncture has shown respectable efficacy and is broadly accepted internationally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, to find more effective therapeutic methods to prevent the return of disease activity many individuals have turned their attention to treatments such as TCM. Currently, clinical experience has been accumulated for TCM treatment of psoriasis [13][14][15][16][17][18][19][50][51][52]. Most significantly, as a type of TCM, acupuncture has shown respectable efficacy and is broadly accepted internationally.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis reported that Chinese medicine was effective for psoriasis vulgaris since it is noninferior to acitretin and it could produce add-on effects when combined with acitretin, as well as reducing the acitretin-induced adverse events [14]. Chinese medicine combined with narrowband ultraviolet B for treating psoriasis also showed improved efficacy [15,16]. Herbal formulae or plant extract topical management were analyzed in other systematic reviews, which showed that topical herbal formulae or plant extracts could improve overall clinical symptoms [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It is based on a completely theoretical system, which has evolved progressively in response to technological developments and lifestyle changes. A series of systematic reviews of TCM in clinical practice have indicated that this approach is effective in the treatment of psoriasis [4][5][6][7][8][9][10], and clinical and experimental data indicate that TCM can modify psoriasis by antagonizing or regulating interleukin (IL) and the IL-23/ IL-17 axis to inhibit the main causal pathways [11].…”
Section: Background and Rationalementioning
confidence: 99%
“…It has been commonly used for dermatitis [13], gastrointestinal disease [14], rheumatoid arthritis [15], diabetic mellitus [16, 17], gynecological disorder [18], and cancer [19, 20] patients. Previous studies showed that CHM plus acitrerin had add-on effect [21] and Chinese herbal bath combined with phototherapy was superior to phototherapy alone [22] for psoriasis. Topical application of Lindioil, extract of Qing-dai (Indigo Naturalis; Baphicacanthus cusia (Nees) Bremek, Polygonum tinctorium Aiton, Isatis indigotica Fortune ex Lindl.)…”
Section: Introductionmentioning
confidence: 99%